Prevalence in the utilization of text message services under the mother and child tracking system of India: a cross sectional study from Pune district, Maharashtra, India - Sharma, Ankita; Shinde, Aakash; Kar, Anita (International Journal Of Community Medicine And Public Health, 2017)
Background: The mother and child tracking system (MCTS) is a surveillance system to track pregnant women and children. It includes a provision of short message service (SMS), that alerts registered beneficiaries about outstanding services. This study determined the prevalence of use of SMS by beneficiaries of MCTS from Pune district, Maharashtra. Methods: A cross-sectional study was carried out among respondents availing antenatal care or immunization services at ten randomly selected primary health centres (PHCs) in Pune district. Data was collected after consent using a semi-structured questionnaire. Data was analyzed using Statistical Package for Social Sciences (19.0 version). Results: The study included 205 pregnant women and 236 parents of children. Almost 66% of respondents owned a mobile phone and majority (91%) were residents in areas with network coverage. Among respondents of nine PHCs, 17% of respondents had heard of, and 14% reported having received a text message of outstanding services on the mobile phone. At one PHC where the auxiliary nurse midwife was sending text message reminders in local language from her mobile phone, 43% respondents were aware of text messaging services and almost 24% respondents reported receipt of text messages. Education level (p<0.00) and possession of mobile phone (p<0.004) were significantly associated with receipt of text messages. Conclusions: Low prevalence of use of text messaging service by beneficiaries stresses the need to increase awareness of these services. Text messages in local language have an advantage over the English language at the community level.